Методи та моделі інтелектуальної підтримки прийняття рішень у автоматизованому керуванні гнучким інтегрованим радіоелектронним виробництвом - Цимбал, О. М. (My University, 2014)
Дисертаційна робота присвячена розв’язанню проблеми створення теорети чних основ інтелектуальної підтримки прийняття рішень у автоматизованих си стемах керування гнучкими інтегрованими системами радіоелектронного виробни цтва для забезпечення їх функціонування в умовах невизначеності робочого простору та характеру виробничих завдань. Вперше запропоновано: концепцію побудови інтелектуальних систем прийняття рішень та метод адаптації стратегій функціонування гнучких інтегрованих роботизованих систем; динамічну, теоретико- множинну та логічну моделі адаптації стратегій функціонування гнучких інте- грованих систем, які дозволяють забезпечити опис функціонування автоматизованої системи керування в умовах динамічного стану робочого простору. Одержали подальший розвиток: метод побудови інтелектуальних систем підтримки прийняття рішень, який дозволяє забезпечити процес прийняття рішень у вигляді уніфікованої пошукової процедури; нечітка та імовірнісна моделі інтелектуального прийняття рі шень, які дозволяють забезпечити оцінку альтернативних шляхів розв’язання завдань автоматизованої системи керування в умовах невизначеності; імітаційна модель опису організації виробництва, яка структурує подання інформації у гнучких інтегрованих системах. Розроблені в дисертації моделі та методи дозволяють забезпечи ти нові проектні рішення з автоматизації процесів керування гнучкими інтегрованими роботизованими системами радіоелектронного виробництва. The thesis is dedicated to the problem of decision-making intellectual support theoretical basis development for control systems of flexible integrated robotized systems of radio-electronic devices production to supply their functioning in conditions of workspace and manufacturing tasks uncertainty. There is proposed the new concept of intellectual support decision-making systems for flexible integrated robotized systems, which provides the support of automatized control processes, the adaptation of developed strategies for technological equipment functioning, taking in account the dynamic state of workspace and of technological system during execution of developed plans. Also, thesis proposes the new method of functioning strategies adaptive planning, which considers the decision-making process in condition of manufacturing system states and goals dynamics. The proposed new dynamic model of adaptive planning considers the interaction of manufacturing system with workspace 39 during implementation of strategies and supplies the description of automatized control system functioning. New model, based on set theory, formulates the basic items of adaptive planning and supplies the description of workspace changes influence to the strategies adaptation. The proposed new logical model, based on predicate’s logics, describes the relationships between the manufacturing system and its workspace, formulates the goals of intellectual control system as required workspace states and defines the construction of logical inference drive for flexible integrated system. In addition, thesis contains the improved model of strategies planning, based on fuzzy theory set, which describes the planning for conditions of flexible integrated system information and of action choice uncertainty and implements the estimation of alternative ways on problem solving. The improved probabilistic model of strategies planning considers the decision-making for integrated manufacturing system as discreet multistage process, defined by Markov-chain method probability evaluation at every, evaluates the alternative ways on problem solving for automatized control system with probabilistic description. The improved method of intellectual decision-making system support defines the inference drive as standardized search procedure, based on framework knowledge structures, defines the order of technological problems solving and supplies the automatic problem solving for closed workspace. The improved informational model of manufacturing describes the working personnel, equipment and flexibility to reconstruct for new goods production. There are developed the basic subsystems of Prolog programming language interpreter, which implements the proposed logical model of strategies planning, used for intellectual decision-making support of automatized control system. Thesis describes the developed software, which implements the proposed theoretical models and contains the subsystems of graphical simulation, of voice and visual control analyzes, of autonomous robot control to support the flexible integrated system automatized control system. Also there is developed the automatized control system software, which implements the proposed methods and models, provides the observation of flexible integrated system dynamics with computer vision tools, supplies the adaptive technological transitions and operations planning and execution, and, as a result improves the efficiency of flexible integrated robotized system functioning.
Keywords: система підтримки прийняття рішень; стратегія функціонування; гнучка інтегрована система; роботизована система; радіоелектронна апаратура; автоматизована система керування; імітаційна модель; інформаційна модель; decision-making support system; functioning strategy; flexible integrated system; robotized system; radio electronic equipment; automitized control system; simulation model; information model